Prevalence Of Low Back Pain and Disability Among Computer Operators Working in The Banks of Peshawar: Low Back Pain and Disability Among Computer Operators - Rehman, Muheeur; Ullah, Kashif; Wajid, Abdul; Zeb, Taimur; Ahmad, Uzair; Rehman, Faiz ur; Tahir, Ahmad (Pakistan Journal of Health Sciences, 2022)
Low-back disorders are linked to awkward postures and hinders both work performance and quality of life. Objective: The aim of this study was to find the prevalence of low back pain and disability among computer operator working in banks of Peshawar. Methods: A cross sectional study was conducted on 300 computer operators. The UBL, HBL and BOK Banks in Peshawar were targeted for recruitment of participants. Non probability convenience sampling technique was used for subject’s enrolment. Both male and female participants with age ranges from 25 to 50yr, working as computer operator in banks were included in study. The Oswestory of low back pain questionnaire and Numeric pain rating scale questionnaire were used to collect the data from the participants. Results: Out of 300 participants, maximum age respondents were 185 (61.7%) range from 25-33 years and minimum age were 26 (8.7%) ranged in 43-50 years. Male enrolled responses were 273 (91.0%) while females were 27 (9.0%). The prevalence of low back pain was 72.3 % among computer operators working in the banks of Peshawar. Based of NPRS, 27.7% computer operator reported no pain while the maximum number of participants i, e., 39.3% (n=118) suffered from mild pain. The maximum participants have minimal disability and reported as 52% (n= 156) while the minimum participants, only 10% (n=30) have sever disability. Conclusions: The current study revealed that, the prevalence of low back pain is high among computer operators working in Peshawar banks.